On competitive balance in the group stage of the UEFA Champions League - Triguero-Ruiz, Francisco Andrés; Ávila-Cano, Antonio Jesús (Wiley, 2022)
This article examines competitive balance in the group stage of the UEFA Champions League over the last two decades (1999/2000–2017/2018). Competitive balance is considered both before and after a competition. Have the groups been designed in such a way as to ensure similar levels of com-petitive balance ex ante? Have the demonstrated strengths (ex post competitive balance) of the different groups been similar over each season? What is the relationship between the competitive balance in the designed groups and that achieved in the same groups after the competition? Are the performance achieved in terms of ex post competitive bal-ance similar to ex ante competitive balance levels? We found that, despite expectations, the groups' ex ante competitive balance was not homogeneous. Although ex ante competi-tive balance serves as a good predictor, on average, of ex post competitive balance, we observed significant differences at the levels of group and seasons. Therefore, it is possible to improve the design mechanism of the groups that make up the group stage of the champions so that they are composed homogeneously in terms of ex ante competitive balance
Keywords: Fútbol; Competitive balance; Distance to competitive balance; Soccer; Truncated cascade distribution; UEFA Champions League